2020
DOI: 10.1098/rsos.191561
|View full text |Cite|
|
Sign up to set email alerts
|

Cytotoxicity studies of Fe3O4nanoparticles in chicken macrophage cells

Abstract: Magnetic Fe 3 O 4 nanoparticles (Fe 3 O 4 -NPs) have been widely investigated for their biomedical applications. The main purpose of this study was to evaluate the cytotoxic effects of different sizes of Fe 3 O 4 -NPs in chicken macrophage cells (HD11). Experimental groups based on three sizes of Fe 3 O 4 -NPs (60, 120 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Cytotoxicity of nanomaterials depends on the concentration, proportion, porosity, aggregation tendency, a chemical affinity for biological structures, chemical surface reactivity and even the shape, size of nanoparticles, and environmental conditions [ 183 , 184 ]. So far, many studies have been conducted on the cytotoxicity of magnetite [ 31 , 111 , 138 , 185 , 186 , 187 , 188 ]. First of all, it has been noticed that the previously mentioned particle size influences the cytotoxicity of magnetite.…”
Section: Challenges In the Development Of Magnetite-based Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxicity of nanomaterials depends on the concentration, proportion, porosity, aggregation tendency, a chemical affinity for biological structures, chemical surface reactivity and even the shape, size of nanoparticles, and environmental conditions [ 183 , 184 ]. So far, many studies have been conducted on the cytotoxicity of magnetite [ 31 , 111 , 138 , 185 , 186 , 187 , 188 ]. First of all, it has been noticed that the previously mentioned particle size influences the cytotoxicity of magnetite.…”
Section: Challenges In the Development Of Magnetite-based Therapiesmentioning
confidence: 99%
“…First of all, it has been noticed that the previously mentioned particle size influences the cytotoxicity of magnetite. When using chicken macrophages, it was found that smaller magnetite particles (60, 120, and 250 nm were used) were more toxic to these cells [ 188 ]. No significant toxicity of particles with a size of 30 μm was detected on HeLa cells and postnatal human fibroblasts [ 138 ].…”
Section: Challenges In the Development Of Magnetite-based Therapiesmentioning
confidence: 99%
“…It is worth noting that cell viability was less than 60% after 48 h, even at low concentrations (20 μg/ml). However, other reports indicated that these nanoparticles had the potential to produce toxic effects in cells, and their toxic effects were related to their size, concentration, time, shape, and the cell type ( Wang et al, 2020 ; Zhang S. et al, 2020 ). Thus, we also verified the cytotoxicity effects of Fe 3 O 4 /GO in BEAS-2B cells, which also belong to human lung epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Silver nanoparticles offer remarkable antibacterial properties and have been employed in food services, building materials, the textile sector, medical devices, personal care items, and washing machines. Silver nanoparticles are utilized in laundry detergents, room sprays, deodorants, wall paints, and indoor air purifiers and water detoxifiers [51]. Due to widespread usage and human exposure to silver nanoparticles, it is feasible for Ag nanoparticles to enter the body and build up in many tissues and organs.…”
Section: Silver Nanoparticlesmentioning
confidence: 99%